Selecting Green Supplier for Perishable Raw Materials using AHP Method at Nunia Boutique Villa Seminyak - Komang Devi Paramita; Nyoman Mastiani Nadra; I Nyoman Winia; I Gede Mudana; Raden Roro Rieta Anggraheni (International Journal of Glocal Tourism, 2023)
Purpose: The aim of this research is to do the selection for green supplier for perishable raw material at Nunia Boutique Villa, Villa with 8 Units Villa located at Seminyak Badung Bali. Research methods: One of the methods that used in this research is Analytical Hierarchy Process (AHP) method with Vendor Performance Index (VPI) is a Quality, Cost, Delivery, Flexibility, and Responsiveness (QCDFR) by adding the Environment Management criteria. This research used the AHP method with the expert choice software. Findings: The final rating of relative importance’s supplier selection criteria was found: the Quality criteria (0.472) was ranked first in the order of priority in the green supplier selection criteria. Implication: The Cost criteria with 0.192, Environment Management criteria (0.102), Delivery criteria (0.091), Flexibility criteria (0.076) and the last criterion is Responsiveness (0.067).